Integrative binocular vision detection method based on infrared and visible light fusion for conveyor belts longitudinal tear. (November 2017) - Qiao, Tiezhu; Chen, Lulu; Pang, Yusong; Yan, Gaowei; Miao, Changyun
Highlights: A novel IBVD method is proposed to detect longitudinal tears of conveyor belts. Based on infrared and visible fusion, the IBVD sensor device is proposed. IBVD method can distinguish tear, scratch and normal situation of conveyor belts. Combining and integrating both light and infrared, IBVD method is more reliable. Abstract: Real-time and reliable detection of conveyor belt longitudinal tear is an important task in mining operations. This paper presents a novel method of Integrative Binocular Vision Detection (IBVD) to detect the longitudinal tears of conveyor belts. Based on infrared and visible fusion, the IBVD sensor device collects the fusion images of the belt. After extracting the tear features by projection method, the progress of potential tears can be evaluated and the tears can be identified. The IBVD method is verified by an experiment platform fulfilling the acquisition, pro-processing and analysis of fusion images for tear detection. The fusion image processing time is less than 18 ms, which satisfies the requirement of real-time online monitoring. Compared to the individual measurement technique of either infrared detection or visible light detection, the average accuracy of the IBVD method reaches up to 96%, the IBVD method is more reliable in tear detection.